Penerapan Keselamatan dan Kesehatan Kerja pada Aktivitas Wisata Berenang Bersama Ikan Hiu (Swim with Shark) di Pulau Serangan, Denpasar Selatan - Julius Simon; Made Sukana (JURNAL DESTINASI PARIWISATA, 2017)
Selection of research is motivated by the increased interest of tourists will kind of attraction travel in Bali. In this kind of travel these attraction are extreme types of tourist activity in Pulau Serangan is, Swim with Sharks. Of course, by choosing the type of extreme travel to swim with the sharks, the great possibility of the risk of accidents caused. Hence the importance of this research study releated to health and safetyof employees and tourist who do this activity in Pulau Serangan. The data used in this research is qualitative data, while the data source in the form of primary data and secondary data. Data was collected through observation, interviews, and library research. And assisted with the descriptive data analysis techniques. In applying the safety and health at tourism activities swim with sharks, this report uses occupational safety and health procedures that apply to employees and tourist who do that tourism activity. Besides, the factors triggering the accident, or the result of the impact and the prevention and mitigation to be part of the discussion of this report. The results showed that the application of occupational safety and health on travel activity swim with sharks being the foremost, so most have applied, only need the addition of some other procedure for the safety of travelers. Keywords: Attraction Tourism, Swim With Shark, Occupational health and safety